solve for M. (m/9)+(2/3)=(7/3)

Question

solve for M.

(m/9)+(2/3)=(7/3)

in progress 0
Eden 5 days 2021-10-08T08:48:08+00:00 1 Answer 0

Answers ( )

    0
    2021-10-08T08:49:08+00:00

    Answer:

    m= 15

    Step-by-step explanation:

    first you subtract 2/3 from both sides (m/9)+(2/3)-(2/3)= (7/3)- (2/3)

    now you will have (m/9)= (5/3)

    to get (m) on its own you have to multiply the both sides by 9

    (m/9) times 9= (5/3) times 9

    m= 45/3 or 15

    Answer check:

    substitute (m) for 15

    (15/9)+(2/3)= (7/3)

    first you should simply (15/9), so all of them will have a common denominator

    (5/3)+(2/3)=(7/3)

    (7/3)=(7/3)

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )